Mapunzungun learning from Mapunche methodologies: perspectives and advances for the revitalization of native languages - Llanquinao Llanquinao, Gabriel; Salamanca Gutiérrez, Gastón; Teillier Coronado, Fernando Salvador (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
In this article the contributions of some studies in relation to the teaching-learning of native languages, especially from the Mapunzugun, are reviewed. For this purpose, different perspectives are considered, although the focus is on those that emerge from the linguistic heritage of the language studied.  Thus, the proposals of teaching methodologies within a context of revitalization, their relationship with applied linguistics and the articulation of the latter with perspectives of language teaching based on the epistemologies and methodologies of the vernacular language are presented. Along with this, some critical considerations regarding the place occupied by Mapunzugun in the context of Intercultural Bilingual Education in Chile and an approach to the vernacular concepts of kimünand rakizuamas key articulators of any teaching-learning methodology based on Mapunche perspectives are presented. A prominent conclusion of this work is that it is necessary to develop and apply language teaching methodologies that come from the socio-cultural practice of the language to be revitalized, relegating the theoretical/pedagogical logics coming from the dominant language to a second level.